The Mediation Effect of Community Empowerment and Good Governance on Forest Productivity: A GSCA Approach - Bambang Hendroyono (UIN Sumatera Utara, 2026)
This study examined how transglobal leadership influenced forest productivity in Indonesia’s community plantation forest program, focusing on the mediating roles of community empowerment and governance. Secondary data from 50 regencies, selected from a population of 127, were analyzed using a Generalized Structural Component Analysis (GSCA) with the mediation testing. The results showed that leadership significantly affected community empowerment and governance, but did not directly influence forest productivity, while both mediating variables had significant positive effects on productivity. The indirect effects accounted for 77.8% of the total effect, indicating that leadership operated primarily through intermediary mechanisms. The model demonstrated satisfactory fit, with FIT = 0.612, AFIT = 0.587, and GFI = 0.93, suggesting adequate explanatory power despite the relatively small sample size. These findings indicated that improvements in forest productivity were achieved through strengthened governance systems and enhanced community capacity, highlighting the importance of integrated institutional and participatory policy interventions.